BIAS GENDER DALAM ATRIBUSI GURU TERHADAP KEBERHASILAN DAN KEGAGALAN AKADEMIK SISWA - Rita Eka Izzaty (Jurnal Penelitian Humaniora, 2003)
Abstract This study was aimed to test statistically the relationship between gender bias and teacher’s attribution towards student’s successes and failures, to measure the strength of influence of the aforementioned variable on the dependent variable, and to explore empirically the existence of such bias in teacher’s attribution. Three hypotheses rose from theoretical analyses to the problem. Firstly, there are relationship between gender bias and teacher’s attribution towards student’s successes and failures. Secondly, there are significant difference between teacher’s attribution toward male and female students in which achievement of male students more attributed to their internal capability, whereas female student’s achievement attributed to external factors, which are degree difficult of the task and luckiness. Thirdly, there are significant differences between teacher’s perception, in respect to their sexes, about suitable areas of career for male and female students. This research was based on quantitative approach, where correlation and difference tests are used. The sample was 68 teachers of Senior High Schools in Yogyakarta, which was chosen according to predetermined criteria. Results showed that level of gender bias among the respondents was low, there was no significant correlation between gender bias and teacher’s attribution towards student’s successes and failures. Moreover samples tended to attribute internal factors as the causes of student’s achievement, in other words, factors found not to be favorite in teacher’s attribution. In addition, this research found that there were differences in their perception about suitable field of career for students, in respects to their sexes, in which those required physical strength and mobility perceived as more suitable for male, such as technical works. On the other hand, fields which require artistry and laboratory works perceived as more suitable for male students. Keywords: gender bias, teacher’s attribution towards student’s successes and failures